2010
DOI: 10.1068/c09175
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Internal and External Characteristics on the Adoption of Climate Mitigation Policies by US Municipalities

Abstract: Many US municipalities are engaged in climate mitigation planning, or efforts to reduce their communities' greenhouse gas (GHG) emissions through land-use, transportation, and energy planning. However, they face a number of procedural and institutional obstacles that limit the adoption and implementation of those plans. The literature identifies some of the factors that lead municipalities to join relevant policy networks, but provides little guidance for overcoming the aforementioned obstacles and adopting po… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
81
1
2

Year Published

2013
2013
2022
2022

Publication Types

Select...
4
2
2

Relationship

1
7

Authors

Journals

citations
Cited by 61 publications
(86 citation statements)
references
References 33 publications
2
81
1
2
Order By: Relevance
“…The opinions of climate change sceptics have been found to impact the course of public debate on climate mitigation strategies (Climate Institute 2010; Leviston and Walker 2010;Nerlich 2010;Oreskes and Conway 2010). The divisive debate poses challenges to effective governance of climate mitigation and adaptation (Few et al, 2007;Amundsen et al 2010;Krause 2011;Pitt 2010;Osberghaus et al 2010;Hobson and Niemeyer, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…The opinions of climate change sceptics have been found to impact the course of public debate on climate mitigation strategies (Climate Institute 2010; Leviston and Walker 2010;Nerlich 2010;Oreskes and Conway 2010). The divisive debate poses challenges to effective governance of climate mitigation and adaptation (Few et al, 2007;Amundsen et al 2010;Krause 2011;Pitt 2010;Osberghaus et al 2010;Hobson and Niemeyer, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…Yet, sometimes the choice to join ICLEI can have as much to do with politics as a genuine desire to reduce GHG emissions. Research has shown that ICLEI members tend to be already predisposed to having concern for environmental issues, and have colleges located within their borders (Pitt, 2010b). In contrast, Reams et al (2012) found that the most important factor for achieving ICLEI milestones was length of ICLEI membership and that factors likely to discourage membership include greater automobile dependency and high levels of hazardous air pollution.…”
Section: Iclei and Ccpmentioning
confidence: 84%
“…Each of these has identified unique attributes of climate action plans such as structure, content, stakeholder involvement and efficacy. Some have studied the variables of political will (Betsill, 2001;Wheeler, 2008), political climate (Leiserowitz, 2006;Bassett & Shandas, 2010;Reams, Clinton, & Lam, 2012), and the trend of environmental policies and programs being created in communities that vote for Democratic/Republican representatives (Hanak, Bedsworth, Swanbeck, & Malaczynski, 2008;Lubell, Feiock, & Handy, 2009;Pitt, 2010b;Portney and Berry, 2010;Hawkins & Wang, 2012) as an element of the research. However, no study was identified that specifically analyzes climate action planning in politically conservative communities as its sole aim.…”
Section: Introductionmentioning
confidence: 99%
“…Some modest correlations between the sustainability indices and the WBI were uncovered, but the connection is less than conclusive: Two of the indices were correlated, and two were not. Of the two which were correlated, "Our Green Cities Index" focuses on the presence of civic programs for environmental stewardship (a good indicator of the political policy atmosphere in the city-recall Pitt [2010]), while the "Popular Science Index" includes "green living" and "green perceptions" in a limited scope (only four measured categories). The two uncorrelated indices, "SustainLane" and the "Green City Index" (GCI), are more comprehensive, and rely more on objective performance indicators, and less on perceptions of sustainability.…”
Section: Quality Of Lifementioning
confidence: 99%
“…This is surprising since commute times may be central to predicting a wide variety of social outcomes. Pitt (2010) used commute times as a measure of AD to complete a statistical model predicting an urban climate change mitigation policy score.…”
Section: Automobile Dependencymentioning
confidence: 99%